Feasibility of sentinel lymph node mapping in ovarian tumors: A systematic review and meta-analysis of the literature - Saeideh Ataei Nakhaei; Sayyed Mostafa Mostafavi; Marjaneh Farazestanian; Malihe Hassanzadeh; Ramin Sadeghi (Frontiers in Medicine, 2022)
Purpose of the reportSince the presence of lymph node metastases upstages the disease and to reduce the morbidity of total lymphadenectomy, sentinel lymph node (SLN) mapping in ovarian mass has been the focus of extensive research. This study aims to review all the literature associated with ovarian SLN mapping and assess the feasibility of ovarian SLN mapping.Materials and methodsPubMed and Scopus were searched using the following keywords: (Sentinel lymph node) AND (Ovary OR Ovarian) AND (Tumor OR Neoplasm OR Cancer). All studies with information regarding sentinel node biopsy in ovaries were included. Different information including mapping material, injection sites, etc., was extracted from each study. In total, two indices were calculated for included studies: detection rate and false-negative rate. Meta-analysis was conducted using Meta-MUMS software. Pooled detection rate, sensitivity, heterogeneity, and publication bias were evaluated. Quality of the studies was evaluated using the Oxford center for evidence-based medicine checklist.ResultsOverall, the systematic review included 14 studies. Ovarian SLN detection rate can vary depending on the type of tracer, site of injection, etc., which signifies an overall pooled detection rate of 86% [95% CI: 75–93]. The forest plot of detection rate pooling is provided (Cochrane Q-value = 31.57, p = 0.003; I2 = 58.8%). Trim and fill method resulted in trimming of 7 studies, which decreased the pooled detection rate to 79.1% [95% CI: 67.1–87.5]. Overall, pooled sensitivity was 91% [59–100] (Cochrane Q-value = 3.93; p = 0.41; I2 = 0%). The proportion of lymph node positive patients was 0–25% in these studies with overall 14.28%.ConclusionSentinel lymph node mapping in ovarian tumors is feasible and seems to have high sensitivity for detection of lymph node involvement in ovarian malignant tumors. Mapping material, injection site, and previous ovarian surgery were associated with successful mapping. Larger studies are needed to better evaluate the sensitivity of this procedure in ovarian malignancies.